GAMBARAN PERILAKU PASIEN SEMBUH TB MDR DI KOTA SEMARANG - Sari, Feby Kumala; Cahyo, Kusyogo; Kusumawati, Aditya (Jurnal Kesehatan Masyarakat (Undip), 2018)
Tuberculosis is still a health problem that causes death. MDR TB in Central Java Province Semarang City from 2014 to 2016 decreased to 16 cases and the last 3 years there are data of patients already recovering from MDR TB. This shows the better handling of MDR TB cases in Semarang city because they are able to get case data and able to accompany the patient from the beginning of the illness until healed. Thexpurpose of this research is to know the picture of patient behavior of MDR TB recovered in Semarang City.Thisxqualitative research uses descriptive approach. By purposive sampling technique got 7 research subject which is patient recovered MDR TB. dataxcollection was done by in-depth interview to 7 research subjects. Validation of data is done by triangulation of source to 16 people. Thexresults of the study indicate that the behavior of patients recovered MDR TB in Semarang City because of routine medication, get attention, and motivation both from within themselves and from the surrounding environment. Have good knowledge and attitude with obedience to take medication accompanied by officer Aisyiyah and health officer. Getting good service facilities and support from families, health workers and Aisyiyah officers greatly affect the patient's behavior to recover from MDR TB.